2023
DOI: 10.1021/acsami.2c20937
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Microkinetic Modeling Unravelling the Performance of Edge-Decorated Nanocarbons for Hydrogen Production from Methane

Abstract: The doping of graphitic and nanocarbon structures with nonmetal atoms allows for the tuning of surface electronic properties and the generation of new active sites, which can then be exploited for several catalytic applications. In this work, we investigate the direct conversion of methane into H2 and C2H x over Klein-type zigzag graphene edges doped with nitrogen, boron, phosphorus and silicon. We combine Density Functional Theory (DFT) and microkinetic modeling to systematically investigate the reaction net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 67 publications
0
9
1
Order By: Relevance
“…Our results were compared with literature reports, aiming to provide a full assessment of GNRs as catalysts for methane dissociation and hydrogen evolution and to provide insights for future works on the catalyst engineering of graphene-based materials. In our previous work ( Xavier et al, 2023 ), we found that decoration of non-metallic heteroatoms on the nanocarbons edges can dramatically increase the regeneration of carbonaceous catalysts, however, the performance for methane decomposition reported here on the pure carbon edges was found to be superior. We expect that the insights provided here aid the engineering of carbon-based catalysts for the catalytic methane decomposition.…”
Section: Introductioncontrasting
confidence: 59%
“…Our results were compared with literature reports, aiming to provide a full assessment of GNRs as catalysts for methane dissociation and hydrogen evolution and to provide insights for future works on the catalyst engineering of graphene-based materials. In our previous work ( Xavier et al, 2023 ), we found that decoration of non-metallic heteroatoms on the nanocarbons edges can dramatically increase the regeneration of carbonaceous catalysts, however, the performance for methane decomposition reported here on the pure carbon edges was found to be superior. We expect that the insights provided here aid the engineering of carbon-based catalysts for the catalytic methane decomposition.…”
Section: Introductioncontrasting
confidence: 59%
“…At the same time, DFT calculations have shortcomings, such as difficulty in accurately predicting weak dispersion forces or high computational demand for larger systems. [123,124] Nevertheless, the combination of DFT and microkinetic modeling is a powerful tool for revealing the working principles of SAAs catalysts and guiding the design of advanced catalysts for sustainable NH 3 production. As the field advances, improvements in computational methods and algorithms for model validation, along with more sophisticated experimental techniques, will further enhance the value of this integrated approach.…”
Section: Liu Et Al Utilized Dft-derived Kinetic Modeling To Investiga...mentioning
confidence: 99%
“…By quantifying the rates at which these reactions occur, kinetic models provide valuable insights into the fundamental steps involved in complex electrochemical processes. [ 45 ] Essentially, kinetic modeling for Li‐mediated NRR involves creating mathematical equations that represent the mechanistic steps of the nitrogen fixation process. These steps may include nitrogen and lithium ions being adsorbed onto the catalyst surface, the transformation of these adsorbed species into reaction intermediates, and their subsequent conversion into ammonia or other products.…”
Section: Evaluation Of Mechanisms By Experiments and Kinetic Modelingmentioning
confidence: 99%